GAMMA-LACTAM FORMATION FROM TRIPEPTIDES WITH ISOPENICILLIN-N SYNTHASE - Baldwin, J; Norris, W; Freeman, R; Bradley, M; Adlington, R; Longfox, S; Schofield, C (1988)
Incubation of isopenicillin N synthase (IPNS) with analogues of the natural substrate [(5S)-5-amino-5-carboxypentanoyl]-L-cysteinyl-D-valine (2) in which the cysteinyl residue was replaced by homocysteine gave epimeric 5-hydroxy γ-lactams (10), with no evidence for the formation of bicyclic products.